2017
DOI: 10.1016/j.pmrj.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Sensation, Perception, and Motor Abilities of the Ipsilesional Upper Limb on Hand Functions in Unilateral Stroke: Quantifications From Biomechanical and Functional Perspectives

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Stroke is one of the main causes of death and the leading cause of disability in adults worldwide [14]. Most poststroke individuals experience a reduction in the function on the affected upper limb [5], related to deficits in force generation, muscular atrophy, joint incoordination, sensitivity disturbances, or spasticity [6]. The reduction in function results in impaired sensorimotor performance during activities of daily living, which may lead to frustration and reinforce compensatory behaviors, such as learned nonuse.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is one of the main causes of death and the leading cause of disability in adults worldwide [14]. Most poststroke individuals experience a reduction in the function on the affected upper limb [5], related to deficits in force generation, muscular atrophy, joint incoordination, sensitivity disturbances, or spasticity [6]. The reduction in function results in impaired sensorimotor performance during activities of daily living, which may lead to frustration and reinforce compensatory behaviors, such as learned nonuse.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with sensory deficits were also found to have affected weight discrimination. [26] It was shown that the CKD patients displayed longer time to discriminate weight differences (6.27±2.05 seconds) than other neurological diseases such as the CTS (3.11±1.02 seconds) and stroke (5.1±1.1 seconds),[11, 12, 27] indicating that the CKD might pose a more serious threat to the weight sensory input.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in FR Norm of the CKD patients was in accordance with the previous studies, which showed larger FR in patients with CTS, peripheral nerve injury, stroke and DM as well. [12, 14, 15, 27]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the duration of the intervention in this study was 6 weeks, with only 15-30 min of MI in each session. The number of intervention sessions might need to be increased to eight, and the duration might need to be prolonged to 45 min to enhance the effectiveness of MI [23]. Second, limb hemiplegia might have had adverse effects in the first-stroke patients.…”
Section: Comparison Of Differences In Activities Of Daily Living (Bi mentioning
confidence: 99%